Excessive phase synchronization in cortical activation during locomotion in persons with Parkinson's disease. (August 2019) - Miron-Shahar, Yael; Kantelhardt, Jan W.; Grinberg, Adam; Hassin-Baer, Sharon; Blatt, Ilan; Inzelberg, Rivka; Plotnik, Meir
Abstract: Introduction: Parkinson's disease (PD) is characterized by gait disturbances, which become severe during the advanced stages of the disease. Though gait impairments in Parkinson's disease have been extensively described in terms of spatiotemporal gait parameters, little is known regarding associated patterns of cortical activity. The objective of the present study is to test if interhemispheric synchronization differs between participants with PD and healthy elderly controls (NPD). We analyzed electroencephalography (EEG) signals recorded during bilateral movements, i.e., locomotion and hand tapping. Methods: Fifteen participants with PD ('OFF' their anti-parkinsonian medications) and eight NPD were assessed during quiet standing, straight-line walking, turning, and hand tapping tasks. Using a 32-electrode EEG array, we quantified the synchronization in periodic cortical activation between the brain hemispheres (interhemispheric phase synchronization; inter-PS). Theta, alpha, beta, and gamma bands were evaluated. Results: In all bands, inter-PS was significantly higher for the PD group as compared with the NPD group during standing and walking ( p < 0.001) and during bimanual tasks ( p = 0.026). Conclusions: Persons with PD exhibit increased inter-PS as compared with NPD participants. These findings support previous evidence from animal studies, that bilateral cortical hypersynchronization emerges from the asymmetric neural degeneration that is at the base of the disease. Future studies should elucidate the long-term temporal development of this hypersynchronization and its clinical relevance (e.g., can it 'serve' as prodromal marker?). Highlights: EEG signals were recorded during walking in persons with PD. Inter-hemispheric synchronization was compared between PD and healthy participants. Excessive PD related inter-hemispheric EEG synchronization was observed. Hyper synchronization presumably emerges from asymmetrical PD related neurodegeneration.